2007
DOI: 10.1007/s00222-007-0065-y
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric groups and expander graphs

Abstract: We construct explicit generating sets Sn andSn of the alternating and the symmetric groups, which turn the Cayley graphs C(Alt(n), Sn) and C(Sym(n),Sn) into a family of bounded degree expanders for all n. This answers affirmatively an old question which has been asked many times in the literature. These expanders have many applications in the theory of random walks on groups, card shuffling and other areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…As we will see in Section 3, Theorem 1.1 is an easy consequence of the following theorem, together with recent results of Kassabov [5] and Ellis-Hachtman-SchneiderThomas [3].…”
Section: Centralizers and Expander Familiesmentioning
confidence: 58%
See 1 more Smart Citation
“…As we will see in Section 3, Theorem 1.1 is an easy consequence of the following theorem, together with recent results of Kassabov [5] and Ellis-Hachtman-SchneiderThomas [3].…”
Section: Centralizers and Expander Familiesmentioning
confidence: 58%
“…In Section 2, we will use a basic property of expander graphs to show that certain ultraproducts D G n of finite groups can be realized as centralizers of finitely generated subgroups in suitably chosen universal sofic groups. Then in Section 3, using recent results of Kassabov [5] and EllisHachtman-Schneider-Thomas [3], we will complete the proof of Theorem 1.1.…”
Section: Introductionmentioning
confidence: 96%
“…In another breakthrough [Kas05b], Kassabov showed that the family of alternating and symmetric groups A n and S n can also be made into a family of boundeddegree expanders. His construction combines ingenious combinatorial arguments with estimates on characters of the symmetric group due to Roichman [Roi96].…”
Section: Cayley Expander Graphsmentioning
confidence: 99%
“…One of the main theorems in this area asserts that all (nonabelian) finite simple groups form a family of expanders. The proof of this result is spread over several papers (16)(17)(18).…”
Section: Application To Expandersmentioning
confidence: 97%